MENGURAI DISKURSUS KEPEMIMPINAN DALAM PERSPEKTIF ISLAM - Ramli Abdul Wahid (Islamijah: Journal of Islamic Social Sciences, 2020)
Abstrak: Studi ini mengkaji konsep pemimpin dalam Islam. Studi ini merupakan studi kepustakaan. Data diperoleh dari kitab-kitab tafsir untuk menemukan bagaimana hakikat kepemimpinan dalam Islam. Data dianalisis dengan metode analisis isi. Secara umum, studi ini membahas kriteria pemimpin dalam Islam dan konsep pemimpin perempuan dalam Islam. Beriman, memiliki visi dan program kerja, mampu menjalankan tugas, diterima oleh umat, tidak diktator dan rendah hati. Dalam konteks pemimpin perempuan, tidak ada kesepakatan apakah perempuan boleh menjadi pemimpin. Banyak pemikir di era modern yang tidak dapat menerima pendapat para ulama klasik yang melarang perempuan menjadi pemimpin. Studi ini diharapkan dapat memberikan kontribusi dan inspirasi bagi kajian-kajian tentang gender di era saat ini. Kata Kunci: Islam, pemimpin, perempuan, Alquran, hadis Abstract: Depicting Leadership Discourse in Islamic Perspective. This study examines the concept of leader in Islambased on the Qur’anic interpretation. This study is a literature study. Data is obtained from the books of Qur’anic exegeses to find out how the nature of leadership in Islam. Data is analyzed by content analysis method. In general, this study discusses the criteria for leaders in Islam as well as the concept of women leaders. It is found that amongst the criteria are having faith or believer, having a vision and working program, being able to carry out tasks, being accepted by the people, not being dictatorial and humble. In the context of women leaders, there is no agreement on whether women may become leaders. Many thinkers in the modern era cannot accept the opinions of classical scholars who forbid women to become leaders. This study is expected to contribute and inspire studies on gender in the contemporary era. Keywords: Islam, leadership, women, Qur’an, hadith